A Novel Three-Polysaccharide Blend In Situ Gelling Powder for Wound Healing Applications - Chiara Amante; Tiziana Esposito; Pasquale Del Gaudio; Veronica Di Sarno; Amalia Porta; Alessandra Tosco; Paola Russo; Luigi Nicolais; Rita P. Aquino (Pharmaceutics, 2021)
In this paper, alginate/pectin and alginate/pectin/chitosan blend particles, in the form of an in situ forming hydrogel, intended for wound repair applications, have been successfully developed. Particles have been used to encapsulate doxycycline in order to control the delivery of the drug, enhance its antimicrobial properties, and the ability to inhibit host matrix metalloproteinases. The presence of chitosan in the particles strongly influenced their size, morphology, and fluid uptake properties, as well as drug encapsulation efficiency and release, due to both chemical interactions between the polymers in the blend and interactions with the drug demonstrated by FTIR studies. In vitro antimicrobial studies highlighted an increase in antibacterial activity related to the chitosan amount in the powders. Moreover, in situ gelling powders are able to induce a higher release of IL-8 from the human keratinocytes that could stimulate the wound healing process in difficult-healing. Interestingly, doxycycline-loaded particles are able to increase drug activity against MMPs, with good activity against MMP-9 even at 0.5 μg/mL over 72 h. Such results suggest that such powders rich in chitosan could be a promising dressing for exudating wounds.